2014
DOI: 10.1111/ases.12113
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid technique for laparoscopic incisional ventral hernia repair combining laparoscopic primary closure and mesh repair

Abstract: Introduction: Incisional ventral hernia is one of the most common surgical complications after laparotomy. Laparoscopic repair of incisional ventral hernia has been conducted recently, and the advantages of this procedure have been reported. However, in large orifice cases, the recurrence rate is increased. To improve recurrence rates in large cases, a hybrid method combining laparoscopic primary closure and mesh repair can be applied. Materials and Surgical Technique: Monofilament thread was inserted into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…[ 4 ] Its been reported that hybrid methods are effective for treating cases of ventral hernias involving a large orifice. [ 5 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 ] Its been reported that hybrid methods are effective for treating cases of ventral hernias involving a large orifice. [ 5 ]…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of our technique is the minimal effect on the scar in the midline incision. The surgical technique we used was comparable to that in a previous report, with some modifications [14] . In the previous report, the subcutaneous threads for closing the defect were tied in the midline where some scar tissue may persist [14] , whereas that of ours were tied in the left lateral side ( Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Regardless of the surgical techniques, we should keep in mind that the recurrence rate is higher for larger hernias measuring 10–15 cm [14] , [17] , [18] . In this case, a favorable surgical outcome was achieved only in a short-term.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sharma et al subsequently argued that a limited-conversion technique offered a safe and viable alternative in laparoscopic incisional hernia repair for patients with a bowel incarcerated hernia sac, or requiring extensive adhesiolysis [12]. Other studies have shown that a hybrid technique (laparoscopy with an additional open procedure using only a small incision) reduced the incidence of postoperative complications in patients with giant ventral hernias [13,14]. Griniatsos et al reported a hybrid technique for recurrent incisional hernia repair [15], while Stoikes et al showed that the hybrid approach could be used in obese patients requiring open adhesiolysis during incisional hernia repair [16].…”
Section: Introductionmentioning
confidence: 99%